Safety and efficacy of warfarin in treating pulmonary embolism / Norhalimah Sudirman - Sudirman, Norhalimah (2015)
Background: This study aimed to evaluate the safety and efficacy of warfarin in treating pulmonary embolism by evaluating the Time in Therapeutic Range with the incidence of bleeding and stroke among patients. Results and discussions: .A total number of 30 patients were included in this study. The TTR of 20 out of 30 patients were found to be outside of range (<75%) with 8 of them experienced bleeding. The 10 remaining patients recorded TTR more than 75% where 3 of them experience bleeding during their warfarin treatment. None of the patients from both group experienced stroke. There were a total of 11 patients who experienced bleeding with 10 of them being minor bleeding. The highest identified occurring reason of INR (International Normalized Range) outside of range was found to be drug-drug interactions which were seen in 9 patients. Conclusion: Warfarin treatment should be maintained within the targeted INR range to avoid its unwanted effect such as bleeding and stroke. Based on the findings of this study, it can be concluded that warfarin is effective in preventing stroke based on the absence of stroke incidence throughout the duration of this study. Maintaining the INR of patient within the targeted range can be a challenge since many factor can contribute to the alteration of INR. Although bleeding incidence were reported among patients in this study, most of the reported incidence involved minor bleeding while the major bleeding incidence was relatively low and there was no reported case of intracranial bleeding.